How organizational actors live out paradoxical tensions through power relations: The case of a youth prison - Wenzel, Matthias; Koch, Jochen; Cornelissen, Joep P.; Rothmann, Wasko; Senf, N. Natalie (Organizational behavior and human decision processes, 2019)
•A critical discursive analysis of qualitative data gathered at a youth prison.•Construction of control and resistance through individual responses to paradox.•Enactment of these power positions through collective responses to paradox.•These micro-dynamics contribute to the macro-level reproduction of the status quo. Drawing on a critical discursive analysis of qualitative data gathered at a juvenile detention facility, this study explores how organizational actors live out paradoxes through enacting power relations. Based on our analysis, we elaborate a theoretical framework that conceptualizes (1) individual, role-based responses to paradox through which actors construct positions of control and resistance; (2) collective responses to paradox through which organizational members enact these power positions; and (3) the macro-level effects of such dynamics. Our findings demonstrate how micro-level power struggles keep paradoxical tensions in play. Furthermore, our study shows how, ironically, such struggles participate in the macro-level reproduction of the status quo.